Analysis of workers' compensation disabling claims in Oregon's seafood preparation and packaging industry, 2007‐2013. Issue 5 (6th March 2017) - Syron, Laura N.; Kincl, Laurel; Yang, Liu; Cain, Daniel T.; Smit, Ellen
Abstract : Background: Few occupational health and safety studies have focused on the US seafood preparation and packaging industry, and none on Oregon's seafood industry. Methods: Oregon workers' compensation (WC) disabling claims data were analyzed. Oregon Employment Department and US Census Bureau data were used as denominators for rates. Results: During 2007‐2013, there were 188 accepted disabling claims, with an average annual rate of 24 claims per 1000 workers. Men experienced a significantly higher rate (27.6 per 1000) than women. The most frequent incident characteristics and circumstances were: by nature—traumatic injuries to muscles, tendons, ligaments, joints (42%); by body part—upper extremities (44%); and by event—overexertion and bodily reaction (48%), and contact with objects and equipment (31%). Conclusion: Analyzing WC disabling claims data provides important preliminary information for understanding workplace hazards to develop control strategies. Reducing traumatic and cumulative injury risk among seafood workers is paramount.